Влияние иностранного капитала банков Украины на развитие экономики страны - Посная, Е.А. (Культура народов Причерноморья, 2014)
Доказано, что увеличение активов иностранных банков способствовало росту их использования в экономике, что несколько смягчило воздействие мирового финансового кризиса. Спорным является взаимосвязь между ростом иностранных активов и увеличением убыточности системы банков Украины в 2009-2011 гг. Проанализированы возможные позитивные и негативные стороны роста иностранного капитала в Украине. Рассмотрено, что активные привлечения банков на иностранных рынках капитала и повышение инфляции на мировых рынках привели к резкому росту кредитных портфелей и усилению валютных дисбалансов, что в свою очередь, стимулирует развитие инфляционных процессов вследствие роста ВВП сверх своего потенциального уровня. Выявлено, что ухудшение финансового положения украинских банков определенным образом связано с ростом активов банков с иностранным капиталом. Сопоставляется такой фактор, как формирование иностранного капитала банков Украины с динамикой формирования ВВП страны. Доказано, что иностранный капитал участвует в создании ВВП, что напрямую способствует развитию экономики. Доведено, що збільшення активів іноземних банків сприяло зростанню їх використання в економіці, що дещо пом'якшило вплив світової фінансової кризи. Спірним є взаємозв'язок між зростанням іноземних активів і збільшенням збитковості системи банків України в 2009-2011рр. Проаналізовано можливі позитивні і негативні сторони зростання іноземного капіталу в Україні. Розглянуто, що активні залучення банків на іноземних ринках капіталу та підвищення інфляції на світових ринках призвели до різкого зростання кредитних портфелів і посилення валютних дисбалансів, що в свою чергу, стимулює розвиток інфляційних процесів унаслідок зростання ВВП понад свій потенційний рівень. Виявлено, що погіршення фінансового становища українських банків певним чином пов'язано з ростом активів банків з іноземним капіталом. Зіставляється такий фактор, як формування іноземного капіталу банків України з динамікою формування ВВП країни. Доведено, що іноземний капітал бере участь у створенні ВВП, що безпосередньо сприяє розвитку економіки. Proven to increase the assets of foreign banks boosted their use in the economy, which is somewhat mitigated the impact of the global financial crisis. Controversial is the relationship between the growth of foreign assets and an increase in loss of banks in Ukraine in 2009 to 2011. Bank capital is the basis of the financial activities of banks. State capital of Ukrainian banks significantly affects the development of the national economy. In the economy of the bulk of the loans. This necessitated a systematic study of the state of the credit market in the management of the lending activities of banks. We prove the high efficiency of credit resources in the economic system of the country. The present work studied the effect of growth in loans for the development of Ukraine's economy by simple and multiple correlation. Revealed that banks are not fully used their increased use of credit resources. Designed to measure debt capacity, which allows you to look for the future and know the demand for credit resources. Identified industries that are most attractive to lenders. The study concluded that the credit is only one of the factors of production, and GDP growth is due to the influence of a combination of factors. There was a growth of loans to the economy. Found that when included in the calculations of the totality of the factors of production, the role of credit resources of banks, which together with the basic and working capital, labor and land resources, participate in the creation of the gross domestic product of Ukraine, has a serious impact on the economic development of the country. The dynamics of a lower interest rate for bank entities. Expensive loans have implications for the country's economy. First of all, they cannot be used for innovative reorganization of production and, therefore, the domestic industry produces products that are of lower quality than the products of Western countries, which overflowed Ukrainian markets. Because of expensive loans due to high interest rates, our products inferior in value, it is more expensive. Banks are not fully used their increased use of credit resources. Consumed loans in the economy, mainly directed to the infrastructure market. So, the greatest share in the volume of loans occupy loans to firms sphere of trade, repair of motor vehicles, household goods and personal consumption. The largest share of loans falls into two regions of Ukraine (Kiev and the Kiev region, Dnepropetrovsk region). Under such conditions, the credit markets in other regions can be considered underdeveloped and their potential and opportunities - unused. Analyzed all the possible positive and negative aspects of the growth of foreign capital in Ukraine.